A Cross-Sectional Survey of Aedes Aegypti and Aedes Albopictus Immature In the Discarded Tires - Gharty Chhetri G.C, Ganga; Banjara, Megha Raj; Ghimire, Prakash; Rijal, Komal Raj (Tribhuvan University Journal, 2024)
Vector surveillances are done periodically, to know the prevalent mosquito in a locality, to predict the outbreak of mosquito-borne diseases, to derive effective vector control strategies, etc. Surveillance of different containers would help to set the threshold level of stegomyia indices to predict the outbreak and infestation level. This study aims to determine the infestation level of dengue vectors Aedes aegypti and Aedes albopictus in discarded tires during June and July 2022. A survey of larvae and pupae in the discarded tires of automobile workshop, of two sites Manohara corridor Sadak and Kalanki was carried out. Stegomyia indices, Container index (CI), and House index (HI) were calculated. The emerged adult mosquitoes were identified morphologically after rearing the pupa and larvae in a plastic cup. In June and July 2022, 11 automobile workshops were visited to inspect the presence of larvae and pupae in the discarded tires. Of the total 44 tires inspected, 11 tires were positive for larvae and pupae. Therefore, the Container index (CI) percentage was 25% and the House index was 36.36%. Of the 410 larvae and pupae reared Aedes aegypti 73.87%, Aedes albopictus 13.48%, and other 12.64% were present in the discarded tires. Ae. albopictus was present only in the discarded tires of the Kalanki site. The dominant vector was Ae. aegypti. The discarded tires are shared as breeding habitat by Ae. aegypti and Ae. albopictus. CI and HI percentages predict the risk of dengue outbreaks in the future.